Modeling the Impacts of Manure on Phosphorus Loss in Surface Runoff and Subsurface Drainage. Issue 1 (1st January 2019) - Wang, Zhaozhi; Zhang, T. Q.; Tan, C. S.; Wang, X.; Taylor, R. A. J.; Qi, Z. M.; Yang, J. W.
Abstract : Simulation of phosphorus (P) transfer from manured agricultural lands to water bodies via surface runoff and subsurface drainage is potentially of great help in evaluating the risks and effects of eutrophication under a range of best management practice scenarios. However, it remains a challenge since few models are capable of providing a reasonably accurate prediction of P losses under manure treatment. The Environmental Policy Integrated Climate (EPIC) model was applied to simulate the impacts on dissolved reactive P (DRP) losses through surface runoff and subsurface drainage from a solid cattle manure–amended corn ( Zea mays L.)–soybean [ Glycine max (L.) Merr.] rotation on a clay loam soil (Vertisol) located in the Lake Erie region. Simulations of DRP loss in surface runoff and tile drainage were satisfactory; however, EPIC did not consider DRP loss directly from manure, weakening its accuracy in the prediction of DRP loss in surface runoff. Having previously drawn on EPIC‐predicted surface runoff to initiate SurPhos (Surface Phosphorus and Runoff Model) predictions of DRP losses strictly in surface runoff, no comparison had been made of differences in manure application impacts on EPIC‐ or SurPhos‐predicted DRP losses—accordingly, this was assessed. The SurPhos improved the estimation of DRP loss in surface runoff (Nash–Sutcliffe coefficient, 0.53), especially when large rain events occurred immediately after or within 6 wk of manure application. Generally, EPIC can capture the impacts of manure application on DRP loss in surface runoff and subsurface drainage; however, coupling of the EPIC and SurPhos models increased the accuracy of simulation of runoff DRP losses. Core Ideas: Simulations of DRP loss in surface runoff and tile drainage using EPIC were satisfactory. Simulations of DRP loss in surface runoff between EPIC and SurPhos were compared. Coupling SurPhos and EPIC improved surface DRP loss prediction with manure addition.